Penerapan model inquratif dalam pembelajaran menulis teks biografi berbantuan media film - Rubiati; Wahyuni Sriwaty (Indonesian Journal of Educational Development, 2020)
The research aims to describe the effectiveness of applying film-assisted inqurative models in writing biographical text summaries. The application of the inqurative model was applied in response to the low effectiveness of learning writing skills. The application of inqurative models uses qualitative research methods. The research data were obtained using observation techniques, interviews, documentation, and learning outcomes tests. Data from the test results were analyzed using Mean technique. While qualitative data were analyzed through triangulation. Learning outcomes obtained show an increase in competence of the class average reaches 87. Completeness of learning outcomes towards the learning component can be described as follows, skilled writing (95%), excellent text structure; educational history of (78.3%),very good; career history (69.6%), very good; problems faced (78.3%), very good; awards (78.3%), very good; and the role models (35%), very good. Improved learning outcomes in the form of changes in attitude (character), such as discipline (78%), good and (21.7%), very good; participation (78%), good and (21.7%) very good; cooperation (100%) good and ideas delivery (95.7%), good. The results of the implementation of the inqurative model illustrate that learning outcomes, both quantity (mastery of knowledge and skills) and quality (learning attitudes and student activity), increase. It can be concluded, that the inqurative model in teaching biography is significantly effective. Penelitian bertujuan untuk mendeskripsikan efektivitas penerapan model inquratif berbantuan film dalam menulis ringkasan teks biografi. Penerapan model inquratif diterapkan sebagai jawaban atas rendahnya efektivitas pembelajaran keterampilan menulis. Penerapan model inquratif menggunakan metode penelitian kualitatif. Data hasil penelitian diperoleh menggunakan teknik observasi, wawancara, dokumentasi, dan tes hasil belajar. Data hasil tes dianalisis dengan menggunakan teknik mean. Sedangkan data kualitatif dianalisis menggunakan teknik triangulasi. Hasil belajar yang diperoleh memperlihatkan terjadinya peningkatan kompetensi hingga rata-rata kelas mencapai 87. Ketuntasan hasil belajar terhadap komponen pembelajaran dapat digambarkan sebagai berikut, terampil menulis: stuktur teks 95% sangat baik, riwayat pendidikan tokoh 78,3% sangat baik, riwayat karier tokoh 69,6% sangat baik, masalah yang dihadapi tokoh 78,3% sangat baik, penghargaan tokoh 78,3% sangat baik, dan keteladanan tokoh 35% sangat baik. Peningkatan hasil belajar berupa perubahan sikap (karakter): disiplin 78% baik dan 21,7% sangat baik, partisipasi 78% baik dan 21,7% sangat baik, kerjasama 100% baik, dan menyampaikan gagasan 95,7% baik. Hasil implementasi model inquratif menggambarkan bahwa hasil pembelajaran, baik secara kuantitatif (penguasaan pengetahuan dan keterampilan) maupun kualitas (sikap belajar) dan keaktifan siswa meningkat. Dapat disimpulkan, bahwa model inquratif dalam pembelajaran meringkat teks biografi sangat efektif.